HUBUNGAN SELF-EFFICACY DAN EMPATI DENGAN ALTRUISME PADA RELAWAN BENCANA DI PMI KOTA BOGOR - Refiana Gunawan, (2021)
Disaster volunteers have an important role in disaster management in Indonesia. The term of selfless help is attached to a volunteer because of their altruism. Altruism is the desire to help the well-being of others and the willingness to do good without thinking about the gain. The purpose of this study was to determine the relationship between self-efficacy and empathy for the altruism of disaster volunteers at PMI Kota Bogor. This study used cross-sectional research design conducted at PMI Bogor City in June 2021. Subjects of this study were 54 disaster volunteers. The sampling method using total sampling. Collecting data using self-efficacy, empathy, and altruism questionnaires. The results of the statistical test showed a significant relationship between self-efficacy and altruism (p-value = 0.001) and a significant relationship between empathy and altruism (p-value = 0.001). Volunteers are expected to increase altruism by utilizing the facilities provided by the institution, such as contributing directly to disaster sites and participating in disasters.